Bologna Process: At the Threshold of the Third Decade - Valentin I. Baidenko (Высшее образование в России, 2018)
The paper reviews a present state of the Bologna reforms in terms of their analysis made at the Paris Conference of European Ministers responsible for higher education. The paper is based on numerous materials presented to the Conference by major organizations and associations engaged in conceptual, methodological and regulatory support of the Bologna reforms (EUA, EURASHE, ENQA, ESU, etc.). Among the main challenges of this Bologna transformation stage are implementing studentcentered approach to education as well as focusing on learning outcomes in terms of the competencebased model. The article notes unevenness of the ongoing reforms, disregard of their implementation cohesiveness and a growing negative impact of the current financial and economic problems. The author dwells on difficulties in acquiring a new pedagogical paradigm which asserts a shift “from teaching to learning” in higher education didactics. There are also difficulties in implementing key Bologna commitments including adoption of a three-cycle structure of higher education, academic and professional recognition of qualifications, internal and external quality assurance. The paper highlights the need for a complex systematic work related to the development of strategies for the digitalization of education. The paper brings the experience of European universities concerning ethical practices, the fight against corruption in academic environment and educational management, eradication of incorrect citation and plagiarism in scientific researches, including usurpation of authorship. The paper concludes with outlining main development directions of the Bologna reforms for their third decade.